Disability Insurance Screening and Worker Outcomes - Alexander Ahammer; Analisa Packham (Institute of Labor Economics (IZA), 2023)
We estimate the returns to more targeted disability insurance (DI) programs in terms of labor force participation, program spillovers, and worker health. To do so, we analyze workers after a workplace injury that experience differential levels of application screening. We find that when workers face stricter screening requirements, they are less likely to receive DI benefits and are more likely to remain in the labor force. We observe no differences in any physical or mental health outcomes. Our findings imply that imposing stricter DI screening has large fiscal benefits but does not yield any detectable health costs, on the margin.
Keywords: I38; I18; J18; J16; 330; disability insurance; retirement; health